Antibacterial activity test of celery leaf (Apium graveolens) extract liquid hand soap against Staphylococcus aureus - Sri Idawati; Adriyan Suhada; Roushandy Asri Fardani; Septadel Arini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Personal and environmental hygiene must be considered to prevent the transmission of COVID-19. One of them is by washing hands with soap. Liquid soap is a skin cleanser made from soap-based ingredients and added surfactants, preservatives, foam stabilizers, fragrances, and dyes. The basic ingredients for soap can be natural, one of which is essential oil. Celery contains essential oils (alinin and allicin), flavonoids, protein, vitamin A, vitamin C, vitamin B, iron, calcium, sulfur, and phosphorus. Essential oil from celery has activity as an antifungal and is active against many bacteria, including Staphylococcus aureus. This study aims to determine the celery extract liquid hand soap has antibacterial activity against Staphylococcus aureus bacteria and the effective concentration of celery leaf extract liquid hand soap on the antibacterial activity of Staphylococcus aureus. The research method was laboratory experimental by testing the antibacterial activity of liquid hand soap formulations of celery leaf extract. The results of the organoleptic test were green in color, in viscous liquid form, and had a distinctive celery aroma. The pH test obtained a pH of 9.4 in the 5% formulation (FI), pH 9.5 in the 10% formulation (FII), and pH 9.3 in the 15% formulation (FIII). Antibacterial activity test FI, FII, FIII, negative control, and positive control resulted in a diameter of 17.1 mm inhibition zone; 23.2 mm; 17.4 mm; 0 mm, and 22.9 mm. The results of the one-way ANOVA test obtained a p-value <0.05, which indicated that H1 was accepted, i.e., liquid hand soap with celery leaf extract had antibacterial activity against Staphylococcus aureus. The Tukey test showed that the diameter of the FII inhibition zone (10% concentration) was close to that of the positive control inhibition zone. The most effective concentration is 10% (FII), with a very strong inhibition category.